Do the Intellectual Property Rights of Importers Matter for Promoting Australian Exports?. (September 2014) - Salim, Ruhul; Al Mawali, Nasser; Islam, Amirul
Abstract This article provides the first empirical evidence on the effects of intellectual property rights (IPRs) and threat of imitation on Australia's export flows. Using data from all of Australia's trading partners over the period 1995–2010, an augmented gravity model is estimated in the context of an unbalanced panel. The empirical findings show that level of IPRs of importing countries and threat of imitation posed by the importing countries is both sensitive to Australian bilateral trade flows. These results therefore support the widely accepted positive nexus between the importance of IPRs and bilateral trade flows.